Expert System for Diagnosing Damage Genset Petbow on PT.Salim Ivomas Pratama Tbk Method Using Certainty Factor (CF) - Yoga, Herman; Simanjorang, R. Mahdalena (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
This study aims to design an expert system applications that are made to provide solutions to users in order to Overcome the cause of damage to the generator set. The mechanism of this program works with the Certainty Factor method, while the method used in this research is to collect information about the generator damage from experts systematically compiled into a database on a computer where the database will Determine the solution of the facts. facts on the generator sets entered into this program. The test results of this program will provide a solution to the user quickly intervening after the user Provides information to the program about the state of the generator that is interrupted or damaged.